The role of obesity in increasing the risk of hypertension in the elderly - Suprapto Suprapto; Zhian Salah Jalal; Ali Syahid Bayau Naka (Edukasi Ilmiah Indonesia, 2024)
Introduction: Obesity has been identified as one of the main risk factors contributing to the increase in hypertension cases, particularly among the elderly. This study aims to analyze the role of obesity in increasing the risk of hypertension in the elderly by examining the relationship between body mass index (BMI) and blood pressure. Methods: This research uses a cross-sectional design, an analytical study that studies the causes of incidents or incidents. Data collection uses a questionnaire. The sample in this study was 64 elderly hypertensive patients in the working data analysis using the chi-square test. Results: This study's results indicate a relationship between obesity (p=0.000) and the incidence of hypertension in the elderly working. The results showed that the elderly with obese status had a significantly higher risk of hypertension compared to the elderly with average weight. Conclusions: These findings underscore the importance of preventing and treating obesity in the elderly to reduce the risk of hypertension and other health complications. This research is expected to contribute to formulating health policies and hypertension prevention programs among the elderly through a practical weight management approach